Relative contribution of drag and lift forces in the separate phases of the front crawl swimming - Gourgoulis, V.; Boli, A.; Aggeloussis, N.; Toubekis, A. G.; Vezos, N.; Kasimatis, P.; Mavrommatis, G. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: The resultant force produced by a swimmer`s hand is a combination of drag and lift forces. The optimal combination of these forces is important, in order as much as possible of the resultant force to be aimed in the swimming direction (Schleihauf, 2004). Although both drag and lift forces are important for the swimming propulsion, it is suggested that, it is more effective when swimmers rely more on drag, rather than on lift forces (Maglischo, 2003). However, there is a lack of data regarding the relative contribution of drag and lift forces in the separate phases of the underwater stroke in front crawl swimming, which was the purpose of the present study. METHODS: Ten female swimmers swam 25 m front crawl with maximal intensity, with pull-buoy and without breathing in the middle of the pool. Four camcorders (60 Hz) were used to record the underwater motion of the right hand, and the digitizing of selected points was undertaken using the Ariel Performance Analysis System. The underwater stroke was divided in three phases: a) entry and catch b) pull and c) push. The hydrodynamic coefficients and the methodology described by Sanders (1999) were used to estimate the propulsive forces of the hand. Two-way analysis of variance for repeated measures was used for the statistical treatment of the data. RESULTS: During the pull phase the mean drag force (7.27 ± 1.89 Í) was significantly (F1,9= 7.590; p < 0.05) greater than lift force (5.37 ± 1.33 Í), while during the push phase no significant (F1,9= 3.829; p= 0.082) differences were found between drag (7.85 ± 1.16 N) and lift forces (8.81 ± 1.84 N). Furthermore, the drag force was not significantly different (F1,9= 0.591; p= 0.355) between the pull and push phases, while the lift force was significantly higher (F1,9= 29.142; p< 0.05) during the push vs. the pull phase. DISCUSSION: Both drag and lift forces are important for appropriate propulsion. However, the drag force is decisive for the propulsion in both propulsive phases of the underwater motion of the hand, while the contribution of lift force was increased during the push phase.